2018
DOI: 10.1200/jco.2017.76.5198
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis-to-Treatment Interval Is an Important Clinical Factor in Newly Diagnosed Diffuse Large B-Cell Lymphoma and Has Implication for Bias in Clinical Trials

Abstract: Purpose Selection bias in clinical trials has consequences for scientific validity and applicability of study results to the general population. There is concern that patients with clinically aggressive disease may not have enrolled in recent diffuse large B-cell lymphoma (DLBCL) trials due to the consent process and the inability to delay therapy for eligibility evaluation. We have examined the diagnosis-to-treatment interval (DTI) and its association with clinical factors and outcome in a clinic-based observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 29 publications
8
84
4
1
Order By: Relevance
“…Therefore, the outcome in the overall population was better than anticipated, suggesting an enrollment bias toward more physically fit patients and patients with better prognosis, a common observation in clinical studies. 26 Despite the optimal outcome in the entire non-GCB DLBCL population, an improvement in younger patients was observed for ibrutinib plus R-CHOP. Ibrutinib plus R-CHOP was associated with treatment benefit in most subgroups, except for patients from the United States and Western Europe, but the event number was too small to draw any conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the outcome in the overall population was better than anticipated, suggesting an enrollment bias toward more physically fit patients and patients with better prognosis, a common observation in clinical studies. 26 Despite the optimal outcome in the entire non-GCB DLBCL population, an improvement in younger patients was observed for ibrutinib plus R-CHOP. Ibrutinib plus R-CHOP was associated with treatment benefit in most subgroups, except for patients from the United States and Western Europe, but the event number was too small to draw any conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies started their follow-up period at the time from diagnosis and others from initiation of first-line treatment. Recently some data has shown that patients who have a more aggressive disease tend to be treated earlier, so there could be selection bias between studies that have a shorter period between time of diagnosis and initiation of treatment versus studies with a longer period [ 54 ]. For future studies it seems important to have a comparable start of the follow-up period and authors should report the interval between diagnosis and start of the treatment to prevent or adjust for this risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, intensive multidrug chemotherapy protocols are associated with risk of life‐threatening acute toxicities and late complications (Oeffinger et al , ; Barnes et al , ; Corazzelli et al , ; Hoelzer et al , ; Ribrag et al , ). Additionally, the favourable results seen in clinical trials using such treatment protocols do not necessarily apply to the broad population of patients in the routine clinical setting, who may be older, frailer, or have urgent need for treatment excluding them from trial inclusion (Maurer et al , ).…”
mentioning
confidence: 99%